People of the book - Brooks, Geraldine (Viking, 2008)
In 1996, Hanna Heath, a young Australian book conservator, is called to analyze the famed Sarajevo Haggadah, a priceless six-hundred-year-old Jewish prayer book that has been salvaged from a destroyed Bosnian library. When Hanna discovers a series of artifacts in the book's centuries-old binding, she unwittingly exposes an international cover up.